Progress in reducing child mortality and stunting in India: An application of the Lives Saved Tool - Alderman, Harold; Nguyen, Phuong Hong; Menon, Purnima (Oxford University Press, 2019)
The Lives Saved Tool (LiST) has been used to estimate the impact of scaling up intervention coverage on undernutrition and mortality. Evidence for the model is largely based on efficacy trials, raising concerns of applicability to large-scale contexts. We modelled the impact of scaling up health programs in India between 2006 and 2016 and compared estimates to observed changes. Demographics, intervention coverage and nutritional status were obtained from National Family and Health Survey 2005–6 (NFHS-3) for the base year and NHFS-4 2015–16 for the endline. We used the LiST to estimate the impact of changes in coverage of interventions over this decade on child mortality and undernutrition at national and subnational levels and calculated the gap between estimated and observed changes in 2016. At the national level, the LiST estimates are close to the actual values of mortality for children <1 year and <5 years in 2016 (at 41 vs 42.6 and 50 vs 56.4, respectively, per 1000 live births). National estimates for stunting, wasting and anaemia at are also close to the actual values of NFHS-4. At the state level, actual changes were higher than the changes from the LiST projections for both mortality and stunting. The predicted changes using the LiST ranged from 33% to 92% of the actual change. The LiST provided national projections close to, albeit slightly below, actual performance over a decade. Reasons for poorer performance of state-specific projections are unknown; further refinements to the LiST for subnational use would improve the usefulness of the tool.